PENDIDIKAN KESEHATAN DALAM MENINGKATKAN PENGETAHUAN KELUARGA UNTUK MENDUKUNG PEMBERIAN ASI EKSKLUSIF - Yenni Kristiana (Jurnal Sains Kebidanan, 2020)
Families like grandmother usually more dominant role of mother and grandmother's lack of knowledge about exclusive breastfeeding causes are not able to provide support to the mother and the effect on the practice of exclusive breastfeeding in the mother. Health education on exclusive breastfeeding at grandma can improve knowledge so grandmother can support exclusive breastfeeding. Objective Identify the influence of health education on family knowledge in an effort to support exclusive breastfeeding. The research design uses quasi-experimental one-group pretest-posttest. The samples with consecutive sampling technique. The subjects were 51 grandmother of infants 0-5 months. Collecting data using questionnaires about the characteristics of respondents and knowledge. Data were analyzed using Wilcoxon sign test. Result is average score of knowledge before health education is 12.61 with a standard deviation of 4.481 and after health education is 16.06 with a standard deviation of 2.469. Different test analysis results showed that the value pretest posttest larger than nothing, is smaller than the value pretest posttest No 44 and equal to the value pretest posttest No 7 with the value Z = -5.797 with a P value of 0.000. So the value of P value 0.05 then Ho is rejected and H1 accepted. There are the influence of health education on family knowledge about the "exclusive breastfeeding" in an effort to support exclusive breastfeeding.